Nursing diagnoses for elderly women vulnerable to HIV/AIDS - Márcia Cristina de Figueiredo Santos; Maria Miriam Lima da Nóbrega; Antonia Oliveira Silva; Greicy Kelly Gouveia Dias Bittencourt
ABSTRACT Objective: Classify the diagnoses in the conceptual framework of vulnerability of Ayres and in the Orem's self-care theory; Elaborate operational definitions of nursing diagnoses for elderly women vulnerable to HIV/AIDS. Method: A descriptive exploratory study, developed from March to December 2016 in the stages: 1. Classification of diagnoses in the conceptual framework of vulnerability of Ayres and in the Orem's self-care theory; 2. Operational definition of nursing diagnoses. Results: 70 nursing diagnoses were classified in the conceptual framework of vulnerability of Ayres and Orem's self-care theory, and their operational definitions were constructed, where 75.7% of these were validated. Final consideration: Diagnoses represent conditions that make older women vulnerable to HIV/AIDS and are linked to their self-care practices. Operational definitions contribute to a systematic approach to care and greater clarity in its implementation.